1999
DOI: 10.1081/jlc-100101724
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Liquid Chromatographic Separation and Quantitation of Stevioside and Its Metabolites

Abstract: A method of analysis using high performance liquid chromatography (HPLC) was developed for the separation and quantitation of the metabolites of stevioside: steviol-16,17α-epoxide, 15α-hydroxysteviol, steviolbioside, isosteviol, and steviol. The separation was carried out on a reversed-phase C18 Nova-Pack column with gradient elution of acetonitrile/water mixture. The applicability of the method was demonstrated in the detection and separation of stevioside and its metabolites found in blood, feces, and urine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…The lower limit of quantification was 2 ng/mL; at this concentration the precision was determined to be <7% and the accuracy was 101% (Table 2). This sensitivity is very much better than that reported by Hutapea et al 11. with a limit of detection of 0.4 μg, and in our experience is about 500 times better than with UV detection in plasma (1 μg/mL).…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…The lower limit of quantification was 2 ng/mL; at this concentration the precision was determined to be <7% and the accuracy was 101% (Table 2). This sensitivity is very much better than that reported by Hutapea et al 11. with a limit of detection of 0.4 μg, and in our experience is about 500 times better than with UV detection in plasma (1 μg/mL).…”
Section: Resultscontrasting
confidence: 54%
“…Analysis of steviol using HPLC‐UV11 is not sufficiently sensitive to detect the low levels of steviol in plasma after oral administration of stevioside at a dose of 0.5 g/kg in rats. Therefore, to investigate the pharmacokinetic and toxicological profiles of stevioside in rats, a sensitive, accurate and reproducible high‐performance liquid chromatography/mass spectrometry (HPLC/MS) method was developed for the quantification of steviol in rat plasma.…”
mentioning
confidence: 99%
“…Steviol glycosides have been purified further by extensive recrystallization, often coupled with preparative RP-HPLC to obtain highly pure compounds. Their subsequent characterization involved not only extensive MS and NMR studies but also the analysis of the cleaved-off sugars by a combination of alkaline (C-19 sugar moieties), and acid hydrolysis (C-13 and C-19 sugar moieties). Specific methods have also been developed for the extraction of steviol glycosides or their metabolites from blood, urine, and feces, as well as from food …”
Section: Steviol Glycosides Occurrence and Diversitymentioning
confidence: 99%
“…Separation of underivatized steviol glycosides became more important after the discovery of rebaudioside A in 1975. From the late 1970s on, steviol glycosides have increasingly been analyzed by HPLC due to the easiness of sample preparation and the more satisfactory separation of stevioside ( 37 ), rebaudioside A ( 38 ), and other steviol glycosides, compared to methodologies based on TLC. Eventually, highly specific HPLC-based analytical methods have evolved for the separation and quantitation of the different steviol glycosides with ever higher resolution and sensitivity, using a variety of different instrumentation (e.g., RP-HPLC, 2D-HPLC, ultra-HPLC, and 2D-ultra-HPLC), columns (e.g., C 18 , , NH 2 , , and HILIC ), mobile phases (e.g., AcCN and MeOH) with or without gradient elution, and detection systems (e.g., UV, MS, and amperometry). Besides HPLC-based methods, other analytical protocols include, for example, high-performance TLC, overpressured layer chromatography, capillary electrophoresis, , high-speed counter-current chromatography, 2D-GC, quantitative 1 H NMR, , near-infrared reflectance spectroscopy, and square-wave polarography .…”
Section: Steviol Glycosides Occurrence and Diversitymentioning
confidence: 99%
“…Hutapea et al have presented an HPLC method for identification of the metabolites of SV found in blood, feces and urine of hamsters after ingestion of SV. The separation was carried out on a reversed phase C18 column with gradient elution of acetonitrile/water mixture, whereas T. Rajasekaran et al have developed a liquid chromatograpy–M/S‐ESI method for the determination of eight components of Stevia.…”
Section: Introductionmentioning
confidence: 99%